Vitamin D supplementation and physical activity of young soccer players during high-intensity training - Skalska, M.; Nikolaidis, P. T.; Knechtle, B.; Rosemann, T. J.; Radziminski, L.; Jastrzebska, J.; Kaczmarczyk. M.; Mysliwiec, A.; Dragos, P.; López-Sánchez, G. F.; Jastrzebski, Z. (Nutrients, 2019)
The aim of this study was to confirm that vitamin D supplementation of young soccer players during eight-week high-intensity training would have a significant effect on their motion activity. The subjects were divided into two groups: the experimental one, which was supplemented with vitamin D (SG, n = 20), and the placebo group (PG, n = 16), which was not supplemented with vitamin D. All the players were subjected to the same soccer training, described as High-Intensity Interval Training (HIIT). The data of the vitamin D status, time motion parameters and heart rate were collected just before and after the intervention. A significant increase in 25(OH)D concentration (119%) was observed in the supplemented group, while the non-supplemented group showed a decrease of 8.4%. Based on the obtained results, it was found that physical activity indicators in the players were significantly improved during small-sided games at the last stage of the experiment. However, taking into account the effect of supplementation with vitamin D, there were no statistically significant differences between the placebo and the supplemented groups; thus, the effect size of the conducted experiment was trivial.